Effects of Magnetically Guided, SPIO-Labeled, and Neurotrophin-3 Gene-Modified Bone Mesenchymal Stem Cells in a Rat Model of Spinal Cord Injury - Rui-Ping Zhang; Ling-Jie Wang; Sheng He; Jun Xie; Jian-Ding Li (Hindawi Limited, 2016)
Despite advances in our understanding of spinal cord injury (SCI) mechanisms, there are still no effective treatment approaches to restore functionality. Although many studies have demonstrated that transplanting NT3 gene-transfected bone marrow-derived mesenchymal stem cells (BMSCs) is an effective approach to treat SCI, the approach is often low efficient in the delivery of engrafted BMSCs to the site of injury. In this study, we investigated the therapeutic effects of magnetic targeting of NT3 gene-transfected BMSCs via lumbar puncture in a rat model of SCI. With the aid of a magnetic targeting cells delivery system, we can not only deliver the engrafted BMSCs to the site of injury more efficiently, but also perform cells imaging in vivo using MR. In addition, we also found that this composite strategy could significantly improve functional recovery and nerve regeneration compared to transplanting NT3 gene-transfected BMSCs without magnetic targeting system. Our results suggest that this composite strategy could be promising for clinical applications.